2021
DOI: 10.1038/s41598-021-85629-0
|View full text |Cite
|
Sign up to set email alerts
|

AptaNet as a deep learning approach for aptamer–protein interaction prediction

Abstract: Aptamers are short oligonucleotides (DNA/RNA) or peptide molecules that can selectively bind to their specific targets with high specificity and affinity. As a powerful new class of amino acid ligands, aptamers have high potentials in biosensing, therapeutic, and diagnostic fields. Here, we present AptaNet—a new deep neural network—to predict the aptamer–protein interaction pairs by integrating features derived from both aptamers and the target proteins. Aptamers were encoded by using two different strategies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 113 publications
(102 reference statements)
0
27
0
Order By: Relevance
“…On the bright side, these algorithms are constantly being refined through the release of new and improved software [ 107 , 108 , 109 ]. Finally, special emphasis should be placed on deep learning methods, whose efficiency has outperformed other methodologies in 3D RNA structure ranking [ 110 , 111 ] and have begun to appear in the computational aptamer field as well [ 112 , 113 ].…”
Section: Nucleic Acid Aptamersmentioning
confidence: 99%
“…On the bright side, these algorithms are constantly being refined through the release of new and improved software [ 107 , 108 , 109 ]. Finally, special emphasis should be placed on deep learning methods, whose efficiency has outperformed other methodologies in 3D RNA structure ranking [ 110 , 111 ] and have begun to appear in the computational aptamer field as well [ 112 , 113 ].…”
Section: Nucleic Acid Aptamersmentioning
confidence: 99%
“…In his study, [23] revealed an innovative deep learning methodology for predicting API that he dubbed AptaNet. AptaNet is one of a kind since it is capable of predicting API by using the sequencebased attributes of aptamers in addition to the physicochemical and conformational properties of targets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to that, we use a deep neural network as well as a system for balancing things out. To determine how effectively AptaNet functions, [23] has conducted a great deal of research and testing. Experiments show that AptaNet has higher accuracy than other methods that were investigated for this study on their 32 benchmark datasets, where Aptamers were encoded utilizing two distinct strategies (k-mer frequency and reverse complement k-mer frequency).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unfortunately, these methods present the drawbacks of increasing the process costs and complexity [ 37 , 45 , 46 ]. Machine learning models have been recently proposed as an additional tool for aptamer design, but up to now, only a few examples of aptamer-protein analyses have been reported [ 47 , 48 , 49 ]. To the best of our knowledge, no machine learning models for small aptamer molecules have been reported and they can have a significant impact on several applications such as DNA, toxin, heavy metal, antibiotic, ion, molecular marker, and virus detection.…”
Section: Introductionmentioning
confidence: 99%